The Inculcation Of Critical Thinking In The Teaching Of Basic Science Education In Selected Schools In Nigeria - Inuwa, Usman Muhammad (2024)
The thesis is an investigative research based on the descriptive qualitative case study of critical thinking manifestations in basic science education level from the philosophical perspectives. Qualitative data was collected from interviews, observation and document analysis, using interview protocol, fieldnotes and documents analysis which were later excerpted, coded, and themed. Further discussion was carried and performed in line with themes analysed. Five basic science teachers, purposely selected on certain inclusion criteria, participated in the study from three different categories of public schools in Nigeria, that served as research sites. The themes were identified and discussed. Generally, the themes revealed that there are no objectives on critical thinking in the basic science education curriculum, teachers’ classroom stated objectives and the assessment/evaluation questions. The themes further revealed basic science as simply a foundational science subject; and some teachers’ non clarity with curriculum objectives. In addition, the themes revealed that the curriculum only have clear provisions for behavioural objectives; Noncritical thinking objectives. It revealed that, no training on critical thinking (for the teachers at the preservice or in service training); the teachers’ noncritical thinking instructions; Teacher - centred classes; Non reflection of high Bloom’s or 5 E’s model; Inadequate resources (for teaching in the research sites). Further, the themes revealed that the teachers’ assessment is guided by the curriculum; Non assessment of critical thinking; and inappropriate questioning strategies.